2023
DOI: 10.1111/cns.14152
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte to high‐density lipoprotein ratio predicts clinical outcomes after acute ischemic stroke or transient ischemic attack

Abstract: Aims The monocyte to high‐density lipoprotein cholesterol ratio (MHR) has emerged as a novel inflammatory biomarker of atherosclerotic cardiovascular disease. However, it has not yet been identified whether MHR can predict the long‐term prognosis of ischemic stroke. We aimed to investigate the associations of MHR levels with clinical outcomes in patients with ischemic stroke or transient ischemic attack (TIA) at 3 months and 1 year. Methods We derived data from the Third China National Stroke Registry (CNSR‐II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Recruited from peripheral blood monocytes into the ischemic hemisphere, these cells differentiate into macrophages and play contrasting roles in the pathophysiology of ischemic stroke [19][20][21][22][23]. Proinflammatory macrophages contribute detrimentally to the acute phase, whereas anti-inflammatory macrophages aid in functional recovery in the later stages [14,[24][25][26][27]. Nevertheless, the associated pathophysiological mechanisms need further clarification.…”
Section: Introductionmentioning
confidence: 99%
“…Recruited from peripheral blood monocytes into the ischemic hemisphere, these cells differentiate into macrophages and play contrasting roles in the pathophysiology of ischemic stroke [19][20][21][22][23]. Proinflammatory macrophages contribute detrimentally to the acute phase, whereas anti-inflammatory macrophages aid in functional recovery in the later stages [14,[24][25][26][27]. Nevertheless, the associated pathophysiological mechanisms need further clarification.…”
Section: Introductionmentioning
confidence: 99%
“…Previous epidemiological studies based on Chinese populations have explored various risk factors for adverse cardiovascular events, particularly acute ischemic stroke [ 11 , 24 ]. Additionally, a nationwide cohort study in the United States revealed the predictive value of MHR for long-term cardiovascular outcomes in the general population, and a follow-up study from Turkey also demonstrated the predictive capability of MHR for long-term outcomes in patients with acute coronary syndrome [ 14 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a relatively new biomarker, the Monocyte to High-Density Lipoprotein-Cholesterol Ratio (MHR) combines two independent CVD risk factors, surpassing the predictive ability of monocyte count alone for CVD and reflecting the balance between chronic inflammation and oxidative stress [ 10 ]. Past epidemiological studies have extensively explored the association between elevated MHR and adverse cardiovascular events, demonstrating efficient predictive power for all-cause and cardiovascular mortality [ 11 14 ]. However, research on its correlation with CKD and CRS is quite limited.…”
Section: Introductionmentioning
confidence: 99%
“…These findings hold substantial importance in devising strategies aimed at reducing MHR levels to prevent adverse cardiovascular outcomes. Furthermore, additional studies [35] have confirmed that elevated MHR levels independently forecasted an unfavourable prognosis and increased all-cause mortality among patients with ischaemic stroke or transient ischaemic attack (TIA). However, to date, to the best of my knowledge, no relationship has been found between MHR and outcomes in patients who did not receive treatment or who received endovascular therapy, pending the need for further research findings to be explored.…”
Section: Mhr Independently Predicted Clinical Prognostic Outcomes In ...mentioning
confidence: 99%